Voltammetric investigation on interaction of Hyaluronic Acid with crystal violet and its analytical application - Zhang, WeiLi; Niu, XueLiang; Zhang, Ping Ping; Sun, Wei (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
In this paper, the interaction of hyaluronic acid (HA) with crystal violet (CV) was investigated carefully by linear sweep voltammetry on the dropping mercury working electrode (DME). In pH 5.0 Britton-Robinson (B-R) buffer solution, CV has a sensitive, well-defined second order derivative linear sweep voltammetric reductive wave at â€“0.85 V (vs. SCE). After adding a certain amount of HA into CV solution, the reductive peak current decreased without any shift of reductive peak potential. Based on the difference in the reductive peak current, a new voltammetric method for the detection of HA was established. The reaction conditions and the electrochemical determination were studied and optimized. Under the optimized conditions, the decrease of peak current showed a good linear relationship with the HA concentration in the range from 10.0 to 40.0 mg/L. The linear regression equation was got as âˆ†ipâ€³(nA)= 84.07 Câ€“527.86Â (mg/L) (n=8, Î³=0.997) and the detection limit was calculated as 2.65 mg/L (3Ïƒ). This new established method was further used to HA determination in the synthetic samples with satisfactory results and good recovery. The stoichiometry of CV-HA complex was calculated and the binding mechanism was also discussed by the electrochemical data.